Experiment-based Learning in The Topic of Natural Acid-Base Indicators During A Limited Face-to-face Learning Process - Sonny Rohimat (Indonesian Journal of Mathematics and Natural Science Education, 2022)
The implementation of limited face-to-face learning is carried out while still complying with health protocols to prevent the spread of Covid-19. The curriculum used is the 2013 curriculum for emergency conditions. The implementation of the distance learning policy for more than two years has caused various problems for both teachers and students. In the subjects of the natural sciences, including chemistry, one of the problems that arises almost everywhere is the achievement of basic competency skills that require the implementation of experimental learning methods. This research was conducted to overcome these problems in line with the policy of implementing limited face-to-face learning by applying practical learning on natural acid-base indicator material. The research was conducted descriptively with the research subject as many as 19 students on a limited schedule of face-to-face learning at school. The research consisted of two stages, i.e., the preparation stage which consisted of curriculum analysis, student analysis, analysis of learning resources, and preparation of learning tools, and the implementation stage, i.e., the experimental learning process through natural acid-base indicator practicum activities which is carried out in the laboratory using a discovery learning model. All stages of learning were carried out well and all students showed a positive attitude towards the competence of activeness and cooperation.